THE CORRELATION BETWEEN STUDENTSâ EXTRAVERSION PERSONALITY AND THEIR WRITING SKILL AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR (A DESCRIPTIVE STUDY) - Sangkala, Ismail (EXPOSURE JOURNAL, 2012)
The Research Question is âIs there any Correlation between Studentsâ Extraversion Personality and their writing skill of Muhammadiyah University of Makassar? âThe Researcher used Descriptive Study; the aims of thus research are to find out the correlation between studentsâ Extraversion Personality and their writing skill. The result of the studentsâ writing test had increased in scores. The mean score of students writing skill is 32, 72 and mean score of personality test is 59, 41. The successful of minimal criteria (KKM) was 70 there were students got very good in writing skill and Personality test studentsâ got balance.Keywords: Correlation, Studentsâ extraversion, Personality, Writing SkillPertanyaan Penelitian adalah "Apakah ada korelasi antara siswa Kepribadian Extraversion dan keterampilan menulis mereka di Universitas Muhammadiyah Makassar?âPeneliti yang digunakan adalah Penelitian Deskriptif; sehingga tujuan penelitian adalah mengetahui hubungan antara Kepribadian Extraversion siswa dan keterampilan menulis mereka. Hasil tes menulis siswa meningkat dalam skor. Rata-rata siswa keterampilan menulis adalah 32, 72 dan berarti skor tes kepribadian adalah 59, 41. Kerangka Kelulusan Minimal (KKM) adalah 70 ada siswa menjadi sangat baik dalam kemampuan menulis dan uji kepribadian siswa mendapat keseimbangan.Kata Kunci: Korelasi, extraversion Mahasiswa, Kepribadian, Menulis Keterampilan